KAJIAN PELAKSANAAN KETENTUAN MINIMAL KONTRAK ANTARA PENGGUNA DAN PENYEDIA JASA KONSTRUKSI BERDASARKAN UUJK 2/2017 - Handityo Basworo; Redityo Januardi (SUPREMASI HUKUM, 2022)
Construction contracts in Indonesia must meet the minimum regulatory points as mandated in Law No.2 of 2017 concerning Construction Services (UUJK 2/2017). The purpose of this regulation is to ensure that the structure of the construction service business in Indonesia guarantees equal rights and obligations between cooperating parties. The results of the preliminary study in UUJK 2/2017, did not find any form of supervision and sanctions for not fulfilling the minimum points so that it has the potential to cause insecurity of the parties' equality. This study aims to describe the efforts of the parties in drafting and the inclusion of minimum points in the contract. The method used is interviews with intermediate qualification contractors in Purbalingga and Banyumas Regencies (case study) and reviewing contract samples regarding the minimum points that must fulfill under UUJK 2/2017. The results showed that the efforts of the parties in drafting the terms of the contract were quite good with the contract drafting mechanism from service users. The service provider then observes and provides input in the form of corrections, deletions, or additional provisions and then negotiated with the service user to be decided together. The percentage of the inclusion of 16 points of the minimum contract provisions is 89.47% of the 19 contract samples. 2 regulatory points are not fulfilled as significant, namely related to building failure and environmental aspects with a percentage of 84.21%. The information obtained is supposed to provide an overview in applying the relevant regulations and theirderivatives. Keywords: construction contract; minimum contract provision; UUJK 2/2017